Cultivating the Constitution in Civic Education for Lower Secondary School (M.1-4) in the Lao People's Democratic Republic - Chotkamonsawad, Pitipat; Mettariganond, Dararat; Manadee, Nathathai (Parichart Journal, 2024)
This article explores the cultivation of constitutional values within the Civic Education textbooks used in lower secondary school (M.1-4) in the Lao People's Democratic Republic. Employing a documentary research methodology, the study focuses on the analysis of Civic Education textbooks that remain central to the current education system in Laos. The primary objective centers on the cultivation of the rights and obligations of citizens, which are categorized into five groups—1) rights and obligations of Children within families, 2) rights and obligations of citizens in relation to peace in society, 3) rights and obligations of Citizens in relation to culture and economy, 4) rights and obligations of citizens, and 5) rights and obligations of citizens to protect the state. All of five groups are designed to ensure the proper exercise of rights and obligations by Lao citizens, as prescribed by law, for the maintenance of societal peace. Additionally, this article finds that the content related to rights and obligations in these textbooks considers the age range of students and incorporates various issues through short stories within the chapters. This approach emphasizes that all Lao citizens, irrespective of their backgrounds, have equal access to their rights and responsibilities. In terms of recommendations, it is suggested that issues related to qualifications and culture should be further studied. While not formally defined in the law, they form a pattern that is implemented alongside legal provisions to enhance the comprehensiveness of civic education.